准零刚度低频隔振技术的研究进展 - 刘琪; 李占龙; 王建梅; 连晋毅; 王瑶 (Jixie qiangdu)
In the field of low-frequency vibration isolation research,the proposed quasi-zero stiffness provides people with new solutions.This paper systematically summarizes the structure and characteristics of various quasi-zero stiffness isolators.The control method and engineering application examples of quasi-zero stiffness isolator are described in detail.The research status of quasi-zero stiffness isolator at home and abroad is compared and analyzed.And look forward to the future development trend of quasi-zero stiffness isolators.Finally,the existing problems and corresponding solutions of the quasi-zero stiffness isolator are described.